Synergistic Extraction of Ga(III) from Chloride Solution by Mixture of Cyanex 272 and Alamine 336 - Zhu, Kailun; Ding, Xiaoxi; Jiang, Jiaxin; Tian, Boning; Guo, Qingjie; Wang, Lingyun (Fine Chemical Engineering, 2023)
Aming to select a suitable system for the synergistic solvent extraction of Ga(III), solvent extraction (SX) experiments were carried out by using acidic organo-phosphorous extractants, namely P204, P507 and Cyanex 272, and their mixtures with neutral extractants (TBP, N503) or amine extractants (Alamine 336). Among the studied mixtures, a remarkable synergistic effect for Ga(III) extraction was resulted by the combination of Cyanex 272 and Alamine 336 and the maximal synergistic enhancement coefficient reached 3.11. Compared to the single Cyanex 272, higher equilibrium pH values were observed when mixture of Cyanex 272 and Alamine 336 was employed. The extraction of hydrogen ions by Alamine 336 during the reaction was considered to be responsible for the synergistic extraction, and thus the the extraction of Ga(III) by Cyanex 272 was promoted. Finally, the synergistic extraction stoichiometry of mixture of Cyanex 272 and Alamine 336 for Ga(III) was projected by slope analysis. Ga(OH)A2 was resulted to be the composition of extracted complexes.